Non-random localization of ribonucleoprotein (RNP) structures within an adenovirus mRNA precursor. - Ohlsson, R I (1982)
Heterogeneous nuclear protein complexes (hnRNP) containing the precursor RNA from the adenovirus early region 2 were analysed to determine the specificity of protein-RNA interaction. RNA precursor sequences were present in isolated hnRNP complexes and endogenous 30S particles. At least 20-40 bases long fragments were protected when RNase A was used to remove unprotected RNA sequences in hnRNA complexes. Similarly around 40 bases of RNA were protected in 30S particles. These sequences represent discrete regions of the adenovirus genome. Especially sequences complementary to the EcoRI-F fragment encoding the first leader and the major intron for the DNA binding protein (DBP) RNA precursor, were analysed in detail. Tentatively, sequences resistant to RNase A were located in the middle of the intron and at the splice-donor junction of the first leader of the DBP precursor RNA. The same sequences were identified irrespective whether hnRNP complexes or 30S particles were used suggesting that 30S particles originate from hnRNP complexes. A 38.000 dalton protein appears to be in direct contact with RNA sequences complementary to the EcoRI-F fragment.